Analisis Sistem Pembiayaaan Mitraguna Pada PT Bank Syariah Indonesia - Nadya Namora Hutabarat; Sugianto Sugianto (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
This research aims to analyze the Mitraguna financing system at PT Bank Syariah Indonesia (BSI). Mitraguna is one of the financing products offered by this sharia bank, and this research aims to understand in depth how this financing system is implemented and its impact on the parties involved. The research method used is a case study with a qualitative approach. Data was collected through interviews with related parties at PT Bank Syariah Indonesia, direct observation, and analysis of documents related to Mitraguna financing. It is hoped that the results of this research will provide a better understanding of Mitraguna's financing mechanism and evaluate its effectiveness and efficiency.Research findings show that the Mitraguna financing system at PT Bank Syariah Indonesia has made a positive contribution to meeting consumer financing needs. However, there are several challenges and obstacles faced in implementing this system, such as complex administrative processes and regulatory changes that can affect the financing scheme. It is hoped that this research can make a positive contribution to PT Bank Syariah Indonesia in improving the quality of Mitraguna's financing services and become a reference for further research in developing sharia-based financing products.